Eight Years' Wanderings in Ceylon - Baker, Samuel White, Sir, 1821-1893 (Salt Lake City, UT : Project Gutenberg, 2000)
"Eight Years' Wanderings in Ceylon" by Sir Samuel White Baker is an exploratory travelogue written during the mid-19th century. This work recounts the author$1 (Bs adventurous experiences and observations while he attempts to settle in Ceylon (now Sri Lanka), engaging deeply with its landscapes, cultures, and challenges. The narrative vividly portrays not only the natural beauty and sportsmanship offered by the island but also Baker's struggles with infrastructure and agriculture during a time of colonial expansion. The opening of the narrative introduces readers to Baker's initial arrival in Colombo, where he is met with disappointment contrasted against his expectations shaped by previous readings about Ceylon's allure. Baker describes his longing to partake in the wild adventures of the island, particularly hunting elephants, and introduces his intentions to settle in Newera Ellia. He vividly shares his observations of the city$1 (Bs stagnation and the lack of vibrancy, alongside encounters that highlight the disparity between expectation and reality in colonial settlements. As he begins to outline his plans for improvement and explore the landscape, the tone reflects both wonder and a sense of hardship as he grapples with local conditions and setbacks, setting the stage for his continued explorations throughout Ceylon. (This is an automatically generated summary.)s
Release date is 2000-01-01
Produced by Garry Gill. HTML version by Al Haines.
Keywords: Sri Lanka -- Description and travel